National Ocean Service Aerial Photographs: Seward Peninsula Coastline - Flight Line 10 (International Arctic Research Center (IARC) Data Archive)
This aerial photograph collection consists of about 1897 frames of color infrared and natural color transparencies. It was flown in the summers of 1976 and 1977 for the Outer Continental Shelf Environmental Assessment Program, at an altitude ranging from about 5,000 - 18,400 feet. ECR prefix indicates color infrared, and CC/ZC indicates natural color. It is filed by flight line. This subset of the aerial photograph collection includes flight lines that included coastline from the Seward Peninsula. Flight lines include numbers 8-14 and 24-40. There are 846 images in this subset, 281 natural color images and 565 color infrared images. The photography may be ordered from the National Archives or duplicated in the National Ocean Service photo lab.